Correction: Copper immobilized at a covalent organic framework: an efficient and recyclable heterogeneous catalyst for the Chan–Lam coupling reaction of aryl boronic acids and amines. Issue 3 (18th January 2019) - Han, Yi; Zhang, Mo; Zhang, Ya-Qing; Zhang, Zhan-Hui
Abstract : Correction for 'Copper immobilized at a covalent organic framework: an efficient and recyclable heterogeneous catalyst for the Chan–Lam coupling reaction of aryl boronic acids and amines' by Yi Han et al., Green Chem., 2018, 20, 4891–4900.